(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
This text is a review of the most recent work by French historian François Dosse. The Saga of French Intellectuals is divided into two volumes, the first of which is the focus of our attention, with the subtitle Proof of History. An analysis inscribed in the History of Intellectuals with a time frame from 1944 to 1968, originally published in 2018 in France, but with a first Brazilian publication only in 2021. In this review, we intend to show how Dosse presented a panorama that indicates the position of intellectuals in France from the liberation of the country from German occupation at the end of the Second World War to the turbulent social and political effervescence of 1968. It is therefore an investigation into the ways in which French intellectuals of the period faced the tensions of the post-war period. More than that, the analysis proposes to invest in the ways in which intellectuals actively participated in the public debate and how this participation interfered in the political, cultural and philosophical thinking of this context.